Dimerization process and elementary excitations in spin–Peierls chains coupled by frustrated interactions - Mastrogiuseppe, Diego Martín (2008)
We consider the ground state and the elementary excitations of an array of spin-Peierls chains coupled by elastic and magnetic interactions. It is expected that the effect of the magnetic interchain coupling will be to reduce the dimerization amplitude and that of the elastic coupling will be to confine the spin one-half solitons corresponding to each isolated chain. We show that this is the case when these interactions are not frustrated. On the other hand, in the frustrated case we show that the amplitude of dimerization in the ground state is independent of the strength of the interchain magnetic interaction in a broad range of values of this parameter. We also show that free solitons could be the elementary excitations when only nearest neighbour interactions are considered. The case of an elastic interchain coupling is analysed on a general energetic consideration. To study the effect of the magnetic interchain interaction the problem is simplified to a two-leg ladder, which is solved using density matrix renormalization group (DMRG) calculations. We show that the deconfinement mechanism is effective even with a significantly strong antiferromagnetic interchain coupling.